Stability-Indicating HPLC Method for Quantification of Isotretinoin Impurities in Complex Semi-Solid Dosage Forms - Madugula, Emmanuel; Patra, Niranjan; Baidya, Tinku (International Journal of Pharmaceutical Investigation, 2026)
Background Isotretinoin, a retinoid derivative of vitamin A, is widely used for the treatment of severe recalcitrant acne, reduces sebum production, suppresses sebaceous gland activity, and exhibits potent anti-inflammatory properties and certain dermatological disorders that do not respond to conventional therapy. Materials and Methods Evaluated a new method using a Supelco Ascentis Express C18 column (150 mm × 4.6 mm, 2.7 µm). Gradient elution was employed with mobile phase A (0.1 mL formic acid in 1000 mL water) and mobile phase B (0.1 mL formic acid in 1000 mL of 60:40 methanol: acetonitrile). Results and Discussion A robust and stability-indicating Reverse-Phase High-Performance Liquid Chromatographic (RP-HPLC) method was developed and validated for the quantitative determination of specified impurities in isotretinoin-containing semi-solid formulations. The method exhibited excellent sensitivity, with quantitation limits of 0.03%, 0.04%, 0.02%, and 0.02% for epoxy impurity, 11,13-di-cis impurity, tretinoin impurity, and isotretinoin, respectively. Validation parameters, including accuracy (85-110% recovery), precision, linearity, and robustness, met ICH guidelines. Conclusion The method efficiently resolves isotretinoin from its known impurities, including epoxy impurity, 11,13-di-cis impurity, and tretinoin impurity, forced degradation studies confirmed the specificity and stability-indicating nature of the method. This method is highly suitable for routine quality control of isotretinoin formulations.
Keywords: HPLC; Impurity Profiling; Isotretinoin; Semi-solid Dosage; Stability-indicating Method; Validation.